Compensation - Gerhart, Barry A.; Newman, Jerry M. (McGrawHill, 2023)
"You can't read a news article or blog today without someone talking about compensation (wages/salaries, but also benefits like health care and retirement). Compensation is uniquely important in organizations because it typically represents the single largest operating cost, especially where employee skills or human capital are the source of competitive advantage (e.g., Google/Alphabet, Facebook; investment banking, law, accounting, and consulting firms; professional sports teams; universities). Compensation is also important because employees regularly report it as the most important factor that goes into their decision of whether to take a job or stay in a job"--